Efisiensi Keputusan Merger Tiga Bank Syariah Di Indonesia Pada Masa Pandemi Covid-19 (Studi Di Bsi Kc Bengkulu Panorama) - Kuta Karmila Utari; Yeni Septiyana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Merger is one of the strategies taken by the company to develop and grow the company. In addition, mergers can create a healthy, efficient and competitive company system. The merger decision was made by the three largest state-owned Islamic banks in Indonesia, namely Bank Rakyat Indonesia Syariah (BRIS), Bank Negara Indonesia Syariah (BNIS), and Bank Syariah Mandiri (BSM). This is a decision that aims to encourage larger Islamic banks so that they can enter the global market and become a catalyst for Islamic economic growth in Indonesia. The decision made during the COVID-19 pandemic is the main step in the context of strengthening the Sharia economy in Indonesia, which is being suppressed by the COVID-19 pandemic. The merger of state-owned Islamic banks will make the merger of Islamic banking better and more efficient with indicators of increasing market share for Islamic banking in Indonesia. With the aim of providing an overview of the impacts as well as opportunities and challenges that will arise from the BSI merger decision during the Covid-19 pandemic at BSI KC Bengkulu Panorama. The merging of three state-owned Islamic banks has an impact on various aspects. This impact occurs on customers, employees and the community. Mergers also have an opportunity, namely increasing assets in banks for merger participants and will expand market penetration. On the other hand, mergers also pose many challenges considering that the COVID-19 has shaken the economy in Indonesia. This study uses a qualitative descriptive research method through interviews, documentation, field research and library research so that it can provide information to solve the problems encountered.